ASSESSMENT OF RISK FACTORS OF PREMATURE BIRTH - A.E. SHKLYAEV; M.V. SEMYONOVA; A.S. LYALINA; I.E. MAKSIMOV (Паёми Сино, 2019)
Objective: Assessment of the significance of possible etiological factors in the development of early-premature birth in the Udmurt Republic.